Representations of Cultural Memory in Alban Berg’s Lulu - Ljubibratić, Vanja (Österreichische Gesellschaft für Musikwissenschaft, 2025)
A study of cultural memory pertains to a collective system through which societies engage with knowledge in multiple ways across their community’s history. Symbolic patterns emerge regarding how individuals interact within the group, which is especially emblematic of the production of art as a reflection of these memory-derived systems. This study investigates how Alban Berg’s opera Lulu is a product of the composer’s cultural memory and, specifically, the way in which Berg harnessed the experience of attending a lecture in 1905 by Viennese satirist Karl Kraus. This experience informed Berg’s conception of the symbolic meaning of Frank Wedekind’s Lulu plays, which he drew upon in the 1920s when he brought those memories to the foreground in his operatic adaptation. What emerges is a new view of Lulu from the perspective of revived memories that played a central role in how Berg readapted his past experience to shape the narrative and character interactions in his opera.
Keywords: oopperat; kulttuurihistoria; muistaminen